LEGAL PROTECTION FOR NOTARIES INVOLVED IN CRIMINAL CASES IN THE DRAFTING OF AUTHENTIC DEEDS - Uyuni, Neng Laura Rakhmatul; Mispansyah (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
A legal uncertainty faced by Notaries when they are summoned or charged in criminal proceedings related to their official duties will be something that worries them. As public officials, Notaries often become suspects in cases involving authentic deeds that were made under lawful authority. Many of these cases arise not from intentional wrongdoing, but from misinterpretations of professional acts as criminal offenses. The main legal issue lies in the ineffective protection mechanism stipulated in Article 66 of the Notary Law. The concept of automatic approval (fictitious positive consent) by the Notary Honorary Council (MKN) creates a serious gap in safeguarding the Notary’s position. Additionally, the lack of substantive assessment standards in the MKN's review process reduces the meaningful protection of Notaries’ legal rights. This research uses a normative juridical approach, analyzing legal protection theory and the concept of justice in professional accountability. The findings suggest the need for regulatory reform, including amendments to the notarial law and institutional strengthening of MKN’s authority. A significant recommendation is the formation of a legal assistance unit within the notarial professional organization to represent and defend notaries under legal threat. The ethical independence of Notaries must be preserved, especially when facing undue pressure from clients, state actors, or law enforcement. Legal protection should not only focus on procedures but also uphold the integrity and neutrality of the notarial profession. These legal improvements are essential to prevent the misuse of criminal law against Notaries and to support a more just legal framework.